Identifying barriers to the educational role of midwives in Cyprus and defining determinants in behaviour terms using the Behaviour Change Wheel: a mixed-method formative study - Middleton, Nicos; Hadjigeorgiou, Eleni; Kolokotroni, Ourania; Christodoulides, Veronika; Koliandri, Ioanna; Nicolaou, Christiana; Papadopoulou, Maria; Kouta, Christiana; Karanikola, Maria; Baum, Alison (My University, 2022)
Τhe Baby Buddy Cyprus webapp was co-created with parents and health professionals within a Participatory Action Research framework. While using Baby Buddy in routine consultations can support the educational role of mother-child healthcare providers (HP), antenatal education (AE) may be currently perceived as a formal activity within the physical space of the antenatal class. We aimed to gain an understanding of influences on midwives engaging in an educational role during routine appointments and identify potential interventions using the Behaviour Change Wheel (BCW) framework.
Keywords: Midwives; Antenatal education; Behaviour change; COM-B; Theoretical domains framework; Formative research; Intervention design